PERPUSTAKAAN MASJID: UPAYA MEMBANGUN KESADARAN INKLUSIF - Hariyah, Hariyah (BACA: Jurnal Dokumentasi dan Informasi, 2015)
The main focus of this paper is to elaborate social inclusion in the mosque library. This paper is a qualitative descriptive approach that intends to know the history and understanding of the mosque library, the role of what is being done mosque libraries, and describes the shape of social inclusion in the mosque library. The conclusion that the mosque library is part of an effort to build awareness of inclusion and empower the community to become more mature in religion and society. This empowerment among others with facilitation, education, and accommodation needs of people of all religious communities without discriminating user community in terms of religion, creed, class, physical and so on, the mosque library is the embodiment of democracy and the means to the community well informed. Mosque Libraries should be able to accommodate the information needs of users, into an open space for social activities, and become lifelong education.